Seasonal Changes in Pesticide Residues in Water and Sediments from River Tano, Ghana. (30th April 2022) - Nyantakyi, Jackson Adiyiah; Wiafe, Samuel; Akoto, Osei
Abstract : Pollution due to pesticide residues has been reported in the downstream of the Tano Basin in the rainy season and has been attributed to the anthropogenic activities upstream. However, data on the seasonal variations in pesticide residues in the upstream of Tano Basin are limited. Seasonal variations in 13 organochlorine pesticide residues, 8 organophosphorus pesticide residues, and 5 synthetic pesticide residues in water and sediment samples of River Tano upstream were assessed through extraction and Varian CP-3800 gas chromatography equipped with a CombiPAL Auto sampler set at ionization mode electron impact methods. Significantly higher pesticide residues were detected in water and sediment samples in the rainy season than the dry season. Permethrin (rainy: 0.007 ± 0.01 mg/kg; dry: 0.008 ± 0.02 mg/kg) and profenofos (rainy: 0.021 ± 0.02 mg/kg; dry: 0.026 ± 0.01 mg/kg) showed higher dry season concentrations in the sediment samples. Two isomers of lindane ( δ -HCH = 0.059 ± 0.24  μ g/L; γ -HCH = 0.002 ± 0.01  μ g/L) were detected in the water in the rainy season, but 3 were detected in the sediment samples ( δ -HCH = 0.004 ± 0.12 mg/kg; γ -HCH = 0.003 ± 0.01 mg/kg; aldrin = 0.001 ± 0.01 mg/kg) suggesting possible illegal use. The detected pesticide residual levels in both water and sediment samples were lower than the maximum residual levels in water and sediment. The Chemical Control and Management Centre of the Environmental Protection Agency should check possible faking and adulteration of banned organochlorine pesticides.